2012
DOI: 10.1021/ie202098q
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Analysis of the Thermal Behavior of an Autothermal C3H8Catalytic Partial Oxidation Reformer

Abstract: In this work, a spatially resolved sampling technique is applied to characterize the performance of a C3H8 CPO reformer and to compare it with that of a CH4 reformer. The case of Rh-coated honeycomb catalysts is examined. The axial profiles show that higher temperatures are reached in C3H8 CPO, especially at the reactor inlet. Surface hot-spot temperatures around 950 °C lead the catalyst to rapid loss of activity. A detailed model analysis is also applied to better understand the reasons for the observed diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
6
19
1
Order By: Relevance
“…Compared to former studies of CPOX of methane on Rh [10,12,18,21,35] and propane on Rh [14,35], the two major observations of this study for higher hydrocarbons have not been reported: the extended region for consumption of oxygen and the delayed formation of hydrogen. For DD and all other fuels which were investigated within our study, we clearly see an indirect formation route for hydrogen via water as intermediate, as has already been suggested for e.g., high hydrocarbons [22].…”
Section: Reaction Zones In Cpox Of Higher Hydrocarbonscontrasting
confidence: 93%
See 2 more Smart Citations
“…Compared to former studies of CPOX of methane on Rh [10,12,18,21,35] and propane on Rh [14,35], the two major observations of this study for higher hydrocarbons have not been reported: the extended region for consumption of oxygen and the delayed formation of hydrogen. For DD and all other fuels which were investigated within our study, we clearly see an indirect formation route for hydrogen via water as intermediate, as has already been suggested for e.g., high hydrocarbons [22].…”
Section: Reaction Zones In Cpox Of Higher Hydrocarbonscontrasting
confidence: 93%
“…For higher hydrocarbons as a fuel, the adsorption and activation of hydrocarbons on the catalytic surface plays an important role in the first reaction zone. CO 2 and H 2 O are formed as total oxidation products in this region, which is true for all studies on CPOX of hydrocarbons [10,12,14,18,21,35]. For CPOX of DD and TMB, CO generation was also observed but no hydrogen.…”
Section: Reaction Zones In Methane Cpoxmentioning
confidence: 63%
See 1 more Smart Citation
“…This evidence is in agreement with the lower contact times (shorter reactors) that are required to reach the thermodynamic equilibrium by increasing the effective diffusivities and catalyst loading/dispersion (see Figures a–d). These trends on effective diffusivities and active surface area are responsible for weakening the effects of pore diffusion on the overall regime governing the macroscale performance, in such a way that the full‐scale reactor becomes gradually controlled by the regimes observed in the absence of diffusion limitations: external transport of O 2 for the oxidation reactions and a mixed external transport–kinetic regime for CH 4 consumption through reforming reactions …”
Section: Resultsmentioning
confidence: 99%
“…The coating proceeded through the dip-coating technique. Further details on synthesis methodology can be found elsewhere [34].…”
Section: Catalyst Synthesis Structural and Morphological Characterizationsmentioning
confidence: 99%